Preparation method and application of La-doped modified BiVO4 piezoelectric photocatalyst
Through the preparation method of La doped modified BiVO4 piezoelectric photocatalyst, combined with the combined effect of piezoelectric and light, the problem of low efficiency of existing BiVO4 photocatalysts in degrading 2,4-dichlorophenol is solved, and a significant improvement in degradation efficiency is achieved.
Patent Information
- Application Number
- CN202411933128.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing BiVO4 photocatalysts have problems with high photocarrier recombination rate, low redox capacity and low absorbable light capacity, making it difficult to efficiently degrade the pollutant 2,4-dichlorophenol in water.
Through the preparation method of La doping modified BiVO4 piezoelectric photocatalyst, the combined action of piezoelectric and light is used to degrade pollutants. The method includes mixing a solution of Bi(NO3)3·5H2O and NH4VO3, adjusting the pH to alkaline, then adding La(NO3)3·6H2O and carrying out a hydrothermal reaction to prepare a La doped modified BiVO4 piezoelectric photocatalyst.
The photocatalytic activity and piezoelectric effect of BiVO4 piezoelectric photocatalyst are improved, the response sensitivity to mechanical stress is enhanced, and the degradation efficiency of 2,4-dichlorophenol is significantly improved.
Smart Images

Figure CN119897090A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric photocatalysts, and in particular relates to a preparation method and application of a La-doped modified BiVO4 piezoelectric photocatalyst. Background Art
[0002] 2,4-Dichlorophenol is an organic compound that is insoluble in water but soluble in organic solvents such as ethanol, ether, chloroform, and benzene. It is often used as a synthetic pesticide and herbicide. After use, it will enter the water environment with the water flow, changing the chemical properties of the water body. In addition, 2,4-dichlorophenol is not easily degraded naturally in water and will exist in the water body for a long time, posing a continuous threat to aquatic life. Therefore, it is urgent to study methods that can efficiently degrade 2,4-dichlorophenol in water.
[0003] Photocatalysis has become one of the promising solutions in the field of water environment remediation due to its advantages such as high stability, environmental friendliness and easy operation. Bismuth vanadate BiVO4, as a new type of catalyst with visible light catalytic activity, has attracted much attention in recent years. However, for single-component photocatalysts, due to their inherent energy level structure, they are still insufficient in practical engineering applications due to limitations in terms of high photocarrier recombination rate, low redox ability and light absorption capacity. Rare earth elements have rich energy levels and special 4f electronic structures. After doping with rare earth elements, the spectral response range of the original photocatalyst can be broadened, and the transfer and separation of photogenerated electrons and hole pairs can be greatly improved, thereby improving the photocatalytic activity. However, the energy level structure of BiVO4 will not be affected by rare earth doping, morphology regulation or heterojunction construction alone. Studies have reported that external electric fields are extremely beneficial to the energy level structure of photocatalytic materials and the transport behavior of photogenerated carriers. However, there are no reports on how to use rare earth elements to prepare BiVO4 catalysts with piezoelectric photocatalytic properties. Summary of the invention
[0004] To solve the above technical problems, the present invention proposes a preparation method and application of La-doped modified BiVO4 piezoelectric photocatalyst. The La-doped modified BiVO4 piezoelectric photocatalyst prepared by the present invention can utilize the combined action of piezoelectricity and light to degrade the pollutant 2,4-dichlorophenol.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a La-doped modified BiVO4 piezoelectric photocatalyst, comprising the following steps:
[0007] (1) Mixing Bi(NO3)3·5H2O and HNO3 solution to obtain a mixed solution a; mixing NH4VO3 and NaOH solution to obtain a mixed solution b; mixing the mixed solution a and the mixed solution b, stirring them first, and then adjusting the pH to alkaline to obtain a mixed solution c;
[0008] (2) Adding La(NO3)3·6H2O to the mixed solution c obtained in step (1) and performing a second stirring, and then performing a hydrothermal reaction to obtain the La-doped modified BiVO4 piezoelectric photocatalyst.
[0009] Beneficial effects: The present invention first uses bismuth nitrate pentahydrate and ammonium metavanadate as raw materials, dissolves bismuth nitrate pentahydrate and ammonium metavanadate in acid solution and alkali solution respectively, then mixes the two, and reacts under suitable pH conditions to prepare a bismuth vanadate precursor solution. Lanthanum nitrate is then added to the bismuth vanadate precursor solution as a raw material. During the hydrothermal reaction, not only is part of lanthanum doped into the bismuth vanadate, but the bismuth vanadate gradually evolves from a flake shape to a spherical shape, the specific surface area is greatly increased, and the number of active sites is also greatly increased, providing favorable conditions for improving its photocatalytic activity.
[0010] Bi(NO3)3+La(NO3)3+NH4VO3→complex containing Bi, La, V
[0011] Complex containing Bi, La, V → precipitation
[0012] Precipitation → Drying → La χ Bi 1-X VO4
[0013] Preferably, in step (1), the molar ratio of Bi(NO3)3·5H2O and NH4VO3 is 1:1, but in order to ensure complete reaction, the amount of ammonium vanadate used may be slightly in excess of the theoretical amount. Preferably, the mass ratio of Bi(NO3)3·5H2O and NH4VO3 is 4.8507:1.1796 (equivalent to a molar ratio of 1:1.0085).
[0014] Preferably, in step (1), the dosage ratio of the Bi(NO3)3·5H2O and HNO3 solution is 0.01 mol:30 mL; and the concentration of the HNO3 solution is 4 mol / L.
[0015] Preferably, in step (1), the usage ratio of the NH4VO3 and NaOH solution is 0.01 mol:30 mL; and the concentration of the NaOH solution is 4 mol / L.
[0016] Preferably, in step (1) and step (2), the first stirring and the second stirring are both performed for 5 hours.
[0017] Preferably, in step (1), the pH is adjusted to 9.
[0018] Preferably, in step (2), the amount of La(NO3)3·6H2O used is 2 to 8 mol % based on the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst.
[0019] Preferably, in step (2), the temperature of the hydrothermal reaction is 180° C. and the time is 12 h.
[0020] The present invention provides a La-doped modified BiVO4 piezoelectric photocatalyst prepared by the preparation method described in the above technical solution, and the La-doped modified BiVO4 piezoelectric photocatalyst has a spherical morphology.
[0021] The present invention also provides the use of the La-doped modified BiVO4 piezoelectric photocatalyst described in the above technical solution in the piezoelectric photocatalytic degradation of 2,4-dichlorophenol.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The present invention changes the surface morphology of BiVO4 by doping BiVO4 with La, and simultaneously reduces the unit cell parameters and grain size of BiVO4, thereby providing suitable adsorption sites for the piezoelectric photocatalytic process, enhancing the light absorption capacity, and simultaneously improving the response sensitivity of the BiVO4 piezoelectric photocatalyst to mechanical stress under the ultrasonic vibration piezoelectric effect. Under the action of mechanical stress, the BiVO4 surface energy band is induced to bend, thereby enhancing the piezoelectric effect, thereby obtaining a La-doped modified BiVO4 piezoelectric photocatalyst that can utilize the combined action of piezoelectricity and light to degrade pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 This is a morphology picture of the BiVO4 catalyst prepared in Comparative Example 1;
[0026] Figure 2 This is a morphology image of the La-doped modified BiVO4 piezoelectric photocatalyst prepared in Example 3;
[0027] Figure 3 XRD patterns of the BiVO4 catalyst prepared in Comparative Example 1 and the La-doped modified BiVO4 piezoelectric photocatalysts prepared in Examples 1 to 4;
[0028] Figure 4The degradation efficiency of BiVO4 catalysts prepared in Examples 1 to 4 and Comparative Example 1 on 2,4-dichlorophenol. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] The embodiment of the present invention provides a method for preparing a La-doped modified BiVO4 piezoelectric photocatalyst, comprising the following steps:
[0032] (1) Mixing Bi(NO3)3·5H2O and HNO3 solution to obtain a mixed solution a; mixing NH4VO3 and NaOH solution to obtain a mixed solution b; mixing the mixed solution a and the mixed solution b, stirring them first, and then adjusting the pH to alkaline to obtain a mixed solution c;
[0033] (2) Adding La(NO3)3·6H2O to the mixed solution c obtained in step (1) and performing a second stirring, and then performing a hydrothermal reaction to obtain the La-doped modified BiVO4 piezoelectric photocatalyst.
[0034] The La-doped modified BiVO4 piezoelectric photocatalyst prepared in the embodiment of the present invention is different from ordinary photocatalysts. Piezoelectric photocatalyst is a catalyst that combines piezoelectric effect and photocatalytic properties. Piezoelectric effect refers to the phenomenon of charge polarization generated by certain crystals when subjected to external pressure. This phenomenon polarizes the surface of ferroelectric materials, transfers the polarized strong electric field to the catalyst surface, and promotes physical and chemical reactions on the catalyst surface. Photocatalysis, on the other hand, uses light energy to excite the catalyst to catalytic reaction, forms an excited state by absorbing light energy, reduces the reaction energy barrier and promotes the reaction. The working principle of piezoelectric photocatalyst mainly depends on the combination of piezoelectric effect and photocatalysis. Under the action of mechanical stress (such as ultrasound), piezoelectric materials generate polarized electric fields to promote charge separation and transfer. At the same time, under illumination conditions, photogenerated electrons and holes move in opposite directions driven by the built-in electric field, effectively separating and enhancing catalytic performance. This mechanism can prevent the piezoelectric polarized charge from being recombined by carriers in the electrolyte, thereby providing a driving force to promote charge separation and transfer.
[0035] In a preferred embodiment, in step (1), the molar ratio of Bi(NO3)3·5H2O to NH4VO3 is 1: 1. The present invention controls the molar ratio of Bi(NO3)3·5H2O to NH4VO3 within the above range, ensuring the smooth synthesis of BiVO4.
[0036] In a preferred embodiment, in step (1), the ratio of Bi(NO3)3·5H2O to HNO3 solution is 0.01 mol:30 mL; the concentration of HNO3 solution is 4 mol / L. The present invention adopts HNO3 solution to dissolve Bi(NO3)3·5H2O, thus avoiding the introduction of impurity ions.
[0037] In a preferred embodiment, in step (1), after the Bi(NO3)3·5H2O and HNO3 solutions are mixed, a magnetic stirring step is further included; the magnetic stirring time is 24 hours.
[0038] In a preferred embodiment, in step (1), the usage ratio of the NH4VO3 and NaOH solution is 0.01 mol:30 mL; and the concentration of the NaOH solution is 4 mol / L.
[0039] In a preferred embodiment, in step (1), after mixing the NH4VO3 and NaOH solutions, a magnetic stirring step is further included; the magnetic stirring time is 24 hours.
[0040] In a preferred embodiment, in step (1) and step (2), the first stirring and the second stirring are both performed for 5 hours.
[0041] In a preferred embodiment, in step (1), the pH is adjusted to 9. The present invention is beneficial for obtaining BiVO4 with a high content of monoclinic phase by adjusting the pH to 9.
[0042] In a preferred embodiment, in step (2), the amount of La(NO3)3·6H2O is 2 to 8 mol%, more preferably 2 to 6 mol%, based on the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst. The present invention changes the surface morphology of BiVO4 by La doping, and simultaneously reduces the unit cell parameters and grain size of BiVO4, thereby improving the piezoelectric photocatalytic efficiency of the catalyst.
[0043] In a preferred embodiment, in step (2), the temperature of the hydrothermal reaction is 180°C and the time is 12 hours. The present invention is conducive to obtaining a La-doped modified BiVO4 piezoelectric photocatalyst with excellent piezoelectric photocatalytic efficiency by controlling the temperature and time of the hydrothermal reaction within the above range.
[0044] In a preferred embodiment, in step (2), the hydrothermal reaction further includes washing and drying steps; the washing is specifically: washing with ethanol and deionized water alternately for 3 times; the drying temperature is 60° C. and the drying time is 12 hours.
[0045] The present invention provides a La-doped modified BiVO4 piezoelectric photocatalyst prepared by the preparation method described in the above technical solution, and the La-doped modified BiVO4 piezoelectric photocatalyst has a spherical morphology.
[0046] The present invention also provides the use of the La-doped modified BiVO4 piezoelectric photocatalyst described in the above technical solution in the piezoelectric photocatalytic degradation of 2,4-dichlorophenol (2,4-DCP).
[0047] The room temperature in the embodiments of the present invention refers to "25±2°C".
[0048] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0049] Example 1
[0050] A preparation method of La-doped modified BiVO4 piezoelectric photocatalyst:
[0051] (1) 4.8507 g Bi(NO3)3·5H2O (0.01 mol) was added to 30 mL of 4 mol / L HNO3 solution and magnetically stirred for 24 h to obtain a mixed solution a; 1.1796 g NH4VO3 (0.01 mol) was added to 30 mL of 4 mol / L NaOH solution and magnetically stirred for 24 h to obtain a mixed solution b; then the obtained mixed solution a and mixed solution b were mixed and magnetically stirred for 5 h, and then the pH of the solution was adjusted to 9, and 2 mol% La(NO3)3·6H2O (based on the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst) was added, and magnetic stirring was continued for 5 h to obtain a mixed solution c;
[0052] (2) The mixed solution c obtained in step (1) was transferred to a stainless steel autoclave with a polytetrafluoroethylene lining, subjected to a hydrothermal reaction at 180° C. for 12 h, and after cooling, washed alternately with ethanol and deionized water for 3 times, and dried at 60° C. for 12 h to obtain a La-doped modified BiVO4 piezoelectric photocatalyst, recorded as 2% La-BV.
[0053] Example 2
[0054] The difference from Example 1 is that in step (1), 4 mol% La(NO3)3·6H2O (calculated as the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst) is added, and the rest is the same as Example 1, recorded as 4% La-BV.
[0055] Example 3
[0056] The difference from Example 1 is that in step (1), 6 mol% La(NO3)3·6H2O (calculated as the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst) is added, and the rest is the same as Example 1, recorded as 6% La-BV.
[0057] Example 4
[0058] The difference from Example 1 is that in step (1), 8 mol% La(NO3)3·6H2O (calculated based on the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst) is added, and the rest is the same as Example 1, recorded as 8% La-BV.
[0059] Comparative Example 1
[0060] A method for preparing a BiVO4 catalyst:
[0061] (1) 4.8507 g Bi(NO3)3·5H2O was added to 30 mL of 4 mol / L HNO3 solution and magnetically stirred for 24 h to obtain a mixed solution a; 1.1796 g NH4VO3 was added to 30 mL of 4 mol / L NaOH solution and magnetically stirred for 24 h to obtain a mixed solution b; then the obtained mixed solution a and mixed solution b were mixed and magnetically stirred for 5 h, and then the pH of the solution was adjusted to 9 and magnetically stirred for 3 h to obtain a mixed solution c;
[0062] (2) The mixed solution c obtained in step (1) was transferred to a stainless steel autoclave with a polytetrafluoroethylene liner, subjected to a hydrothermal reaction at 180° C. for 12 h, and after cooling, was washed alternately with ethanol and deionized water for 3 times, and dried at 60° C. for 12 h to obtain a BiVO4 catalyst.
[0063] Comparative Example 2
[0064] The difference from Example 3 is that in step (2), the hydrothermal reaction is carried out at 160° C. for 12 h, and the rest is the same as Example 3.
[0065] Comparative Example 3
[0066] The difference from Example 3 is that in step (2), the hydrothermal reaction is carried out at 200° C. for 12 h. The rest is the same as Example 3.
[0067] Comparative Example 4
[0068] The difference from Example 3 is that in step (2), the hydrothermal reaction is carried out at 180° C. for 10 h, and the rest is the same as Example 3.
[0069] Comparative Example 5
[0070] The difference from Example 3 is that in step (2), the hydrothermal reaction is carried out at 180° C. for 14 h, and the rest is the same as Example 3.
[0071] Figure 1 This is a morphology of the BiVO4 catalyst prepared in Comparative Example 1. Figure 1 It can be seen that the morphology of the BiVO4 catalyst prepared in Comparative Example 1 is block-like.
[0072] Figure 2 This is a morphology of the La-doped modified BiVO4 piezoelectric photocatalyst prepared in Example 3. Figure 2 It can be seen that the morphology of the La-doped modified BiVO4 piezoelectric photocatalyst prepared in Example 3 of the present invention is a regular spherical shape.
[0073] Figure 3 The XRD patterns of the BiVO4 catalyst prepared in Comparative Example 1 and the La-doped modified BiVO4 piezoelectric photocatalyst prepared in Examples 1 to 4 are shown in FIG. Figure 3 It can be seen that due to La 3+ The ionic radius is larger, when La 3+ Doping into the lattice of bismuth vanadate will replace part of Bi 3+ At the same time, due to La 3+ Radius greater than Bi 3+ , causing the unit cell to expand to a certain extent, resulting in greater distortion and stress in the lattice. When the doping amount reaches a certain level, the accumulation of this stress prompts the crystal structure to transform into a more stable hexagonal system to reduce the energy of the system, and ultimately changes bismuth vanadate from the monoclinic system (83-1699) to the hexagonal system (83-1812). La doping reduces the unit cell parameters and grain size of BiVO4, providing suitable adsorption sites for the piezoelectric photocatalytic process and enhancing the light absorption capacity; at the same time, under the piezoelectric effect of ultrasonic vibration, La doping improves the response sensitivity of BiVO4 to mechanical stress, and under the action of mechanical stress, induces the bending of the BiVO4 surface energy band, enhances the piezoelectric effect, and thus improves the piezoelectric photocatalytic efficiency.
[0074] Degradation experiment of 2,4-dichlorophenol in wastewater:
[0075] 2,4-dichlorophenol was uniformly dispersed in an aqueous solution to prepare a 2,4-dichlorophenol solution with a concentration of 10 mg / L as a target pollutant. The BiVO4 catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were used as catalysts, respectively. A 300 W xenon lamp was used as a light source to simulate sunlight illumination conditions.
[0076] Take 100 mL of the above target pollutant and 50 mg of BiVO4 catalyst respectively, put the weighed BiVO4 catalyst into the target pollutant, mix evenly, then irradiate the mixed solution under the light of a 300W xenon lamp and ultrasonicate at an ultrasonic frequency of 45kHZ for 60 minutes to end the degradation experiment.
[0077] The reaction solution was taken and the concentration change of 2,4-dichlorophenol was measured by UV spectrophotometer at 285nm. The degradation efficiency was calculated. The results are shown in Figure 4 and Table 1; wherein, the calculation formula of degradation efficiency is:
[0078] η=(C0-C) / C0×100%
[0079] Where C0 and C are the initial concentration and 60-min concentration of the reactants, respectively, in mg / L.
[0080] Figure 4 The degradation efficiency of 2,4-dichlorophenol by the BiVO4 catalyst prepared in Examples 1 to 4 and Comparative Example 1 is shown in FIG. Figure 4 It can be seen that the degradation efficiency of 2,4-DCP by the BiVO4 catalyst prepared in comparative example 1 is low, only 42.27%, while the degradation efficiency of 2,4-DCP by the BiVO4 catalyst doped with La is significantly improved. As the La doping ratio increases, the degradation efficiency of 2,4-DCP by the La-doped modified BiVO4 piezoelectric photocatalyst gradually increases. When the La doping amount is 6 mol%, the degradation efficiency of 2,4-DCP within 60 minutes is the highest, reaching 89.75%. After the La doping amount continues to increase to 8 mol%, the degradation efficiency of 2,4-DCP within 60 minutes drops to 83.51%. The possible reasons are 1. Changes in the crystal structure: Excessive La doping will cause a significant distortion in the crystal structure of bismuth vanadate. When La ions enter the lattice, they will replace part of the Bi ions. 1. The La doping amount may form a layer of La oxide or hydroxide on the surface of bismuth vanadate, which covers the active sites of the catalyst, hinders the contact and adsorption of pollutant molecules on the catalyst surface, and inhibits the photocatalytic reaction.
[0081] Table 1 Degradation efficiency of 2,4-dichlorophenol by catalysts prepared in Example 3 and Comparative Examples 2 to 5
[0082]
[0083] It can be seen from Table 1 that Comparative Examples 2 and 3 changed the temperature of the hydrothermal reaction, and the degradation efficiency of the obtained BiVO4 catalyst for 2,4-dichlorophenol was reduced by 15.54% and 10.82% respectively compared with Example 3; Comparative Examples 4 and 5 changed the time of the hydrothermal reaction, and the degradation efficiency of the obtained BiVO4 catalyst for 2,4-dichlorophenol was reduced by 10.51% and 8.54% respectively compared with Example 3.
[0084] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing La-doped modified BiVO4 piezoelectric photocatalyst, characterized in that: The following steps are involved: (1) Mixing Bi(NO3)3·5H2O and HNO3 solution to obtain a mixed solution a; mixing NH4VO3 and NaOH solution to obtain a mixed solution b; mixing the mixed solution a and the mixed solution b, stirring them first, and then adjusting the pH to alkaline to obtain a mixed solution c; (2) Adding La(NO3)3·6H2O to the mixed solution c obtained in step (1) and performing a second stirring, and then performing a hydrothermal reaction to obtain the La-doped modified BiVO4 piezoelectric photocatalyst.
2. The method for preparing the La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the molar ratio of Bi(NO3)3·5H2O to NH4VO3 is 1:
1.
3. The method for preparing the La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the dosage ratio of the Bi(NO3)3·5H2O and HNO3 solution is 0.01 mol:30 mL; and the concentration of the HNO3 solution is 4 mol / L.
4. The method for preparing the La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the usage ratio of the NH4VO3 and NaOH solution is 0.01 mol:30 mL; and the concentration of the NaOH solution is 4 mol / L.
5. The method for preparing La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (1) and step (2), the first stirring and the second stirring are both performed for 5 hours.
6. The method for preparing La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (1), the pH is adjusted to 9.
7. The method for preparing La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (2), the amount of La(NO3)3·6H2O used is 2 to 8 mol % based on the amount of La in the La-doped modified BiVO4 piezoelectric photocatalyst.
8. The method for preparing La-doped modified BiVO4 piezoelectric photocatalyst according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 180° C. and the time is 12 h.
9. The La-doped modified BiVO4 piezoelectric photocatalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The La-doped modified BiVO4 piezoelectric photocatalyst has a spherical morphology.
10. Use of the La-doped modified BiVO4 piezoelectric photocatalyst according to claim 9 in piezoelectric photocatalytic degradation of 2,4-dichlorophenol.